Copolymers, compositions and uses thereof

By polymerizing monomers from specific biological sources, a new copolymer is prepared. The application of this copolymer in adhesives and coatings can meet more sustainable and environmentally friendly needs while maintaining good mechanical properties and optical properties, solving the problem of difficult replacement of petroleum-based raw materials in the prior art.

CN119768441APending Publication Date: 2025-04-04ARKEMA FRANCE SA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380063909.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-07
Filing Date
2023-09-04
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing (meth)acrylic copolymers have shortcomings in meeting more sustainable, environmentally friendly, energy-saving and green technology needs, especially while maintaining good optical and mechanical properties, it is difficult to completely replace petroleum-based raw materials.

Method used

A new copolymer is prepared by polymerizing a monomer mixture containing 2-octyl (meth)acrylate, 2-methylbutyl acrylate, 3-methylbutyl acrylate and isoborne (meth)acrylate, which can exhibit similar or better mechanical properties and optical properties to conventional petroleum-based copolymers while having the advantages of renewable resources.

Benefits of technology

The copolymer is capable of providing films with 95% or higher transmittance and 0.5% or lower haze in electronic and touch screen applications, and its excellent balance of mechanical properties and optical properties is suitable for the development of sustainable products that minimize environmental and social impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The present invention relates to a copolymer obtained by polymerizing a monomer mixture comprising: (a) at least one monomer selected from the group consisting of 2-octyl (meth) acrylate, 2-methylbutyl acrylate and 3-methylbutyl acrylate; (b) isobornyl (meth) acrylate; (c) optionally, at least one carboxyl-functional ethylenically unsaturated monomer; and (d) optionally at least one ethylenically unsaturated monomer other than (a), (b) and (c). Compositions comprising the copolymers and their use in adhesives and coatings are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to copolymers obtained by polymerizing specific monomers that may be of renewable origin, ie monomers of bio-origin, compositions comprising said copolymers, and their use, in particular in adhesives and coatings. Background Art

[0002] (Meth)acrylic copolymers are a general term for copolymers obtained by polymerizing two or more monomers containing (meth)acryloyl functional groups (—CO—C (R 1 )=CH2, where R 1 For H or methyl), such as acrylic acid, methacrylic acid, its esters, and its amides. The polymers of this diversified category can be used for many kinds of products, including paints, coatings, textiles, adhesives, plastics, and even cosmetics and personal care products. Through a variety of building blocks (building blocks) and different ester functionalities that can be used for polymer synthesis, the diversity (versatility) of (meth) acrylic polymers is made possible. Chemists select appropriate hard monomers and soft monomers to construct (meth) acrylic copolymers with specific attributes for a variety of end-use applications. For example, (meth) acrylic copolymers can be used to prepare pressure-sensitive adhesives (PSAs) in the form of emulsions, solvent-born systems, or radiation-cured systems. Due to a large number of choices of acrylic and methacrylic comonomers, the resulting product shows a good balance of UV tolerance, transparency, custom viscosity, and rigidity.

[0003] Most of the raw materials currently used to prepare (meth)acrylic copolymers are still petroleum-based. For example, 2-ethylhexyl acrylate (2-EHA), which is derived from petroleum and is therefore unsustainable, can be easily copolymerized with a wide variety of other (meth)acrylic or vinyl monomers and imparts a low glass transition temperature (Tg) to the copolymer (the homopolymer of 2-EHA has a Tg of -70°C).

[0004] Today, the latest challenge is to meet the demand for more sustainable, environmentally friendly, energy-saving and greener technologies. Replacing oil / petroleum-based raw materials with bio-based or renewable ingredients can significantly help reduce the carbon footprint of the final product. A lot of research has been done to synthesize and commercialize new bio-derived materials derived from renewable resources such as plants. Examples of monomers that can be bio-derived include 2-octyl (meth)acrylate, 3-methylbutyl acrylate, 2-methylbutyl acrylate, isobornyl (meth)acrylate, itaconic acid and its esters, etc.

[0005] There is increasing interest in utilizing bio-derivable monomers for environmentally friendly products and processes. Although some efforts have been made to replace all or part of the petroleum-derived raw materials with bio-derivable monomers in the preparation of (meth)acrylic copolymers, there remains a need for new (meth)acrylic copolymers that exhibit both good optical properties (e.g., clarity and low haze) and mechanical properties (e.g., peel strength, holding power, and aging stability) that can be used as adhesives or coatings in electronic and touch screen applications. Summary of the invention

[0006] The first object of the present invention is to provide a copolymer. The copolymer of the present invention is obtained by polymerizing a monomer mixture, based on the total weight of the monomer mixture, the monomer mixture comprises:

[0007] (a) 45 to 95% by weight, in particular 45 to 90% by weight, 48 to 80% by weight, or 50 to 70% by weight, of at least one monomer selected from 2-octyl (meth)acrylate, 2-methylbutyl acrylate, 3-methylbutyl acrylate, and mixtures thereof;

[0008] (b) 5 to 55% by weight, in particular 10 to 55% by weight, 20 to 52% by weight, or 30 to 50% by weight, of isobornyl (meth)acrylate;

[0009] (c) 0 to 5 wt %, in particular 0 to 2 wt %, 0 to 1 wt %, or even 0 wt % of at least one carboxyl-functional ethylenically unsaturated monomer; and

[0010] (d) 0 to 30% by weight, in particular 0 to 20% by weight, 0 to 10% by weight, or 0 to 5% by weight of at least one ethylenically unsaturated monomer other than (a), (b) and (c).

[0011] A second object of the present invention relates to a composition comprising the copolymer of the invention.

[0012] Another object of the present invention relates to the use of the composition of the present invention in the preparation of an adhesive or coating or as an adhesive or coating. Compositions comprising the copolymer according to the present invention may have similar or better mechanical properties and optical properties than conventional petroleum-based compositions. At the same time, since the copolymer of the present invention can be prepared based on renewable resources, it can be used to develop sustainable products that minimize environmental and social impacts.

[0013] The present invention also provides an article comprising at least one film formed by curing the composition of the present invention, the film having a transmittance of 95% or more and a haze of 0.5% or less. DETAILED DESCRIPTION

[0014] The invention will now be described in more detail in the following description without limitation.

[0015] As used herein, the term "ethylenically unsaturated compound" refers to a compound containing a polymerizable carbon-carbon double bond. A polymerizable carbon-carbon double bond is a carbon-carbon double bond that can react with another carbon-carbon double bond in a polymerization reaction. The polymerizable carbon-carbon double bond is typically contained in a group selected from the group consisting of acrylates (including cyanoacrylates), methacrylates, acrylamides, methacrylamides, styrenes, maleates, fumarates, itaconates, allyls, propenyls, vinyls, and combinations thereof, preferably selected from acrylates, methacrylates, and vinyls, more preferably selected from acrylates and methacrylates. The carbon-carbon double bonds of benzene rings are not considered to be polymerizable carbon-carbon double bonds.

[0016] In this specification, the term "(meth)acrylic" refers to acrylic, methacrylic, or a mixture thereof. (Meth)acrylic groups encompass (meth)acrylate groups and (meth)acrylamide groups. The term "(meth)acrylate" refers to acrylate, methacrylate, or a mixture thereof. The term "(meth)acrylamide" refers to acrylamide, methacrylamide, or a mixture thereof.

[0017] In this specification, the term "bio-based" or "bio-derived" is used to describe a material, substance, or monomer that is derived from a renewable source, such as a plant, as far as possible, and can therefore be considered a material of renewable origin. A material of biological origin can be characterized by its biorenewable carbon content (%BRC). The %BRC of a material refers to the proportion of the biomass-derived carbon content in the total carbon content of the material. The calculation formula for %BRC is as follows:

[0018]

[0019] For the copolymers according to the invention, “carbon of biological origin” means in particular the amount of carbonation components of biological origin carried out to prepare the copolymers, and “fossil carbon” means in particular the amount of carbonation components obtained from fossil sources carried out to prepare the copolymers.

[0020] In the present specification, the monomers used to prepare the copolymer of the present invention may be of biological origin. Such monomers include, but are not limited to, 2-octyl (meth)acrylate, 2-methylbutyl acrylate, 3-methylbutyl acrylate, and isobornyl (meth)acrylate.

[0021] For example, 2-octyl (meth)acrylate can be prepared from 2-octanol and (meth)acrylic acid, in particular in the presence of an esterification catalyst of the acid type containing sulfur, such as methanesulfonic acid, and at least one polymerization inhibitor. Alternatively, it can be prepared by an ester exchange reaction between a light (meth)acrylate, such as methyl (meth)acrylate or ethyl (meth)acrylate, and 2-octanol. Advantageously, 2-octanol can be produced by treating ricinoleic acid derived from castor oil with sodium hydroxide, followed by distillation in order to remove sebacic acid. A process for preparing 2-octyl acrylate by direct esterification is described in particular in application WO 2013 / 064775.

[0022] On the other hand, 2-methylbutyl acrylate and 3-methylbutyl acrylate can be prepared from 2-methylbutyl alcohol and 3-methylbutyl alcohol and acrylic acid, respectively, in particular in the presence of an esterification catalyst of the acid type containing sulfur, such as methanesulfonic acid, and at least one polymerization inhibitor. Alternatively, they can be prepared by transesterification between light acrylic acid esters, such as methyl acrylate or ethyl acrylate, and 2-methylbutyl alcohol or 3-methylbutyl alcohol. Advantageously, 2-methylbutyl alcohol and 3-methylbutyl alcohol can be derived from fusel alcohols, which are byproducts of alcohol fermentation of plants, such as fruits or cereals.

[0023] Isobornyl (meth)acrylate is usually synthesized by reacting camphene with (meth)acrylic acid in the presence of an acid catalyst and at least one inhibitor. Camphene is one of the most common terpenes in nature, which appears as colorless crystals with a distinct pungent odor of camphor oil. It is common in many plants, such as the essential oils of cypress, valerian, holy basil, nutmeg, sage, ginger, orange blossom, and rosemary.

[0024] Copolymer

[0025] The copolymer of the present invention is obtained by polymerizing a monomer mixture, which comprises or consists of the following, based on the total weight of the monomer mixture:

[0026] (a) 45 to 95% by weight, in particular 45 to 90% by weight, 48 to 80% by weight, or 50 to 70% by weight, of at least one monomer selected from 2-octyl (meth)acrylate, 2-methylbutyl acrylate, 3-methylbutyl acrylate, and mixtures thereof;

[0027] (b) 5 to 55% by weight, in particular 10 to 55% by weight, 20 to 52% by weight, or 30 to 50% by weight, of isobornyl (meth)acrylate;

[0028] (c) 0 to 5 wt %, in particular 0 to 2 wt %, 0 to 1 wt %, or even 0 wt % of at least one carboxyl-functional ethylenically unsaturated monomer; and

[0029] (d) 0 to 30% by weight, in particular 0 to 20% by weight, 0 to 10% by weight, or 0 to 5% by weight of at least one ethylenically unsaturated monomer other than (a), (b) and (c).

[0030] The total weight of components (a)+(b)+(c)+(d) may account for 100% by weight of the monomer mixture.

[0031] Component (a) consists of at least one monomer selected from the group consisting of 2-octyl (meth)acrylate, 2-methylbutyl acrylate, 3-methylbutyl acrylate, and mixtures thereof.

[0032] In one embodiment, component (a) consists of a single monomer selected from 2-octyl (meth)acrylate, 2-methylbutyl acrylate, and 3-methylbutyl acrylate.

[0033] Alternatively, component (a) may consist of a mixture of 2-octyl (meth)acrylate and at least one monomer selected from 3-methylbutyl acrylate, 2-methylbutyl acrylate, and mixtures thereof. In particular, based on the total weight of component (a), component (a) may consist of:

[0034] (a1) 1 to 99% by weight of 2-octyl (meth)acrylate; and

[0035] (a2) 1 to 99% by weight of 3-methylbutyl acrylate and / or 2-methylbutyl acrylate.

[0036] The total weight of components (a1) + (a2) may account for 100% of the weight of component (a).

[0037] The weight ratio of components (a1) and (a2) is not particularly limited and can be adjusted according to the expected characteristics of the copolymer, such as Tg and %BRC. In a preferred example, based on the gross weight of component (a), component (a) can be composed of 30 to 99 wt % of 2-octyl (meth) acrylate and 1 to 70 wt % of 3-methylbutyl acrylate and / or 2-methylbutyl acrylate. In a more preferred example, based on the gross weight of component (a), component (a) can be composed of 50 to 99 wt % of 2-octyl (meth) acrylate and 1 to 50 wt % of 3-methylbutyl acrylate and / or 2-methylbutyl acrylate.

[0038] Component (b) consists of isobornyl (meth)acrylate. Isobornyl (meth)acrylate is a high Tg and highly hydrophobic monomer. The bicyclic structure of isobornyl (meth)acrylate can lead to improved mechanical properties and thermal stability of the copolymer of the present invention. Component (b) can consist of isobornyl acrylate (IBOA) and / or isobornyl methacrylate (IBOMA). In one embodiment, component (b) consists of IBOA. In another embodiment, component (b) consists of IBOMA. IBOMA may be more preferred than IBOA because of concerns that IBOA is an allergen, while IBOMA has low skin irritation and high Tg, which can contribute to high modulus and retention when used in cured products.

[0039] Component (c) is composed of at least one carboxyl-functional (-COOH) ethylenically unsaturated monomer. The carboxyl-functional ethylenically unsaturated monomer may be an ethylenically unsaturated monocarboxylic acid or dicarboxylic acid, such as (meth) acrylic acid. The presence of component (c) can improve the copolymer adhesion when the copolymer is used in an adhesive, especially an adhesive intended to be applied to a polar substrate such as a metal or glass substrate. However, the presence of component (c) can result in a copolymer with a high acid value, which is not suitable for use in electronic devices because it can cause corrosion on the metal surface, especially in an environment of high temperature and / or high humidity. For example, when a copolymer with a high acid value is used in an adhesive for electronic devices, it can corrode circuits and indium tin oxide (ITO) conductive layers. Therefore, the weight percentage of component (c) present in the monomer mixture can be adjusted according to the end-use application of the copolymer of the present invention.

[0040] In some embodiments, the monomer mixture may be substantially free of component (c). "Substantially free of component (c)" means that the monomer mixture comprises less than 0.5 wt%, less than 0.2 wt%, less than 0.1 wt%, less than 0.01 wt%, less than 0.001 wt%, or even 0 wt% of component (c), based on the total weight of the monomer mixture. As discussed in the above paragraphs, in the absence of component (c), the copolymer prepared by component (a), component (b), and optional component (d) may be suitable for use in adhesives for electronic devices.

[0041] Alternatively, when the monomer mixture includes component (c), the amount of component (c) may be 0.5 to 5 wt %, specifically 0.5 to 3 wt % or 1 to 2 wt %, based on the total weight of the monomer mixture.

[0042] Component (d) consists of at least one ethylenically unsaturated monomer other than the monomers mentioned in components (a), (b) and (c). Examples of suitable monomers that may be included in component (d) are (meth)acrylamide; alpha olefins; vinyl ethers; allyl ethers; styrene and other aromatic vinyl compounds; diesters of ethylenically unsaturated dicarboxylic acids such as maleic acid, fumaric acid, mesaconic acid, citraconic acid, aconitic acid, or itaconic acid; C1-C20 alkyl (meth)acrylates other than 2-octyl (meth)acrylate, 2-methylbutyl acrylate and 3-methylbutyl acrylate, such as methyl (meth)acrylate, ethyl (meth)acrylate, (meth)acrylate, ethyl (meth)acrylate, styrene and other aromatic vinyl compounds; butyl acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate; cyclic (meth)acrylates other than isobornyl (meth)acrylate, such as cyclohexyl (meth)acrylate, phenyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate; -phenoxyethyl ester; N-vinyl pyrrolidone; N-vinyl caprolactam; substituted (meth) acrylamides, such as N-methyl (meth) acrylamide, N-ethyl (meth) acrylamide, N-isopropyl (meth) acrylamide, N-cyclohexyl (meth) acrylamide, N-cyclopentyl (meth) acrylamide, N-methoxymethyl (meth) acrylamide, N-butoxymethyl (meth) acrylamide, N,N-dibutyl (meth) acrylamide, N-butyl (meth) acrylamide, N,N -diethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-octyl(meth)acrylamide, N-decyl(meth)acrylamide, N-dodecyl(meth)acrylamide, N-octadecyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-tert-butyl(meth)acrylamide, N-isobutyl(meth)acrylamide, N,N,3,3-tetramethylacrylamide, N-phenyl(meth)acrylamide, N-(meth)acryloylmorpholine; and mixtures thereof. The selection of monomers in component (d) can be based on the desired characteristics of the copolymer of the present invention, such as Tg and functional groups.

[0043] In some embodiments, component (d) may include at least one monomer selected from a crosslinking monomer or a functional monomer. The presence of a crosslinking or functional monomer helps to prepare a copolymer with a high degree of crosslinking and excellent mechanical properties (e.g., its anti-elongation). When used in an adhesive or coating, a copolymer with a high degree of crosslinking can contribute to the water resistance or chemical resistance of the formed film.

[0044] Examples of crosslinking monomers include:

[0045] - ethylenically unsaturated monomers bearing a carbonyl group, which can react with a compound bearing at least two amino groups, preferably at least two hydrazide groups, such as diacetone (meth)acrylamide, 2-(acetoacetoxy)ethyl (meth)acrylate, 2-(acetoacetoxy)propyl (meth)acrylate, 3-(acetoacetoxy)propyl (meth)acrylate, 4-(acetoacetoxy)butyl (meth)acrylate, 2,3-di(acetoacetoxy)propyl (meth)acrylate, diacetone (meth)acrylate, acetone (meth)acrylate, allyl acetoacetate, vinyl acetoacetate, acetoacetamide, methyl vinyl ketone, ethyl vinyl ketone, butyl vinyl ketone, (meth)acrolein, crotonaldehyde, and formylstyrene;

[0046] - ethylenically unsaturated compounds carrying hydroxyl groups which are reactive with polyisocyanates, for example hydroxyalkyl(meth)acrylates (especially 2-hydroxyethyl(meth)acrylate or 2-hydroxypropyl(meth)acrylate) or N-hydroxyalkyl(meth)acrylamides (especially N-(2-hydroxyethyl)(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-methyl-N-(2-hydroxyethyl)(meth)acrylamide or N-ethyl-N-(2-hydroxyethyl)(meth)acrylamide);

[0047] - ethylenically unsaturated compounds carrying siloxane groups, which can react with the copolymer chain carrying siloxane groups, for example vinyltrimethoxysilane, vinyldimethoxymethylsilane, vinyltriethoxysilane, vinyltripropoxysilane, vinyltriisopropoxysilane, vinyltri(methoxyethoxy)silane, vinyltributoxysilane, vinyltriacetoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, methacryloxymethyltrimethoxysilane, 3-methacryloxypropyltri(2-methoxyethoxy)silane, vinyltrichlorosilane, vinylmethyldichlorosilane, vinyltri(2-methoxyethoxy)silane;

[0048] - compounds carrying at least two ethylenically unsaturated functional groups which can react with the copolymer chain carrying ethylenic unsaturation, for example polyfunctional (meth)acrylates, polyvinyl monomers or compounds comprising both (meth)acrylic groups and vinyl groups, more particularly allyl (meth)acrylate, diallyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, ethylene glycol di(meth)acrylate, diallyl phthalate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol triallyl ether, dicyclopentenyl-6-oxyethyl (meth)acrylate, glycerol tri(meth)acrylate;

[0049] and mixtures thereof.

[0050] Examples of functional monomers include:

[0051] - acetoxyethyl (meth)acrylate,

[0052] - an ethylenically unsaturated monomer carrying a phosphonic acid (-P(=O)(OH)2) group, a phosphonate (-P(=O)(OR)2) group, a sulfonic acid (-S(=O)2OH) group, a sulfonate (-S(=O)2OR) group, or a phosphate (-OP(=O)(OR)2) group, wherein each R is independently a counterion, a hydrogen atom, or an optionally substituted hydrocarbyl phosphate or phosphonate functional group,

[0053] - ethylenically unsaturated monomers carrying urea functional groups,

[0054] - ethylenically unsaturated monomers carrying an amine function,

[0055] and mixtures thereof.

[0056] In some embodiments, the monomer mixture may be substantially free of component (d).

[0057] In the practice of the present invention, the copolymers of the present invention can be obtained by conventional polymerization techniques, including but not limited to solvent polymerization, dispersion or emulsion polymerization, solvent-free bulk polymerization, and radiation polymerization, including processes using ultraviolet light, electron beams, and gamma radiation. A polymerization initiator, particularly a thermal initiator or a photoinitiator, can be used in an amount effective to polymerize the comonomer.

[0058] The copolymers of the invention are preferably not prepared by dispersion or emulsion polymerization, ie in an aqueous medium and in the presence of one or more polymerization initiators and optionally one or more surfactants.

[0059] The copolymers of the present invention are preferably prepared by solvent polymerization, ie in an organic solvent medium and in the presence of one or more polymerization initiators.

[0060] Examples of suitable organic solvents include hydrocarbon organic solvents such as n-hexane, n-heptane, cyclohexane, methylcyclohexane, benzene, toluene or xylene; halogenated organic solvents such as trichloroethylene or methyl chloroform; esters such as ethyl acetate, isopropyl acetate, n-butyl acetate, or sec-butyl acetate; and mixtures thereof. The amount of the organic solvent may be adjusted so that the amount of the copolymer is 10 to 80% by weight, and preferably 20 to 50% by weight, based on the total amount of the copolymer and the organic solvent.

[0061] The example of suitable polymerization initiator includes azo compound and peroxide. Azo compound is a compound containing the azo group of formula -N=N-. The example of suitable azo compound is azobisisobutyronitrile (AIBN). Peroxide compound is a compound containing the peroxide group of formula -OO-. Peroxide compound can be particularly selected from hydrogen peroxide, hydroperoxide (ROOH), dialkyl or alkyl aryl peroxide (ROO-R '), peracid (RC (=O)-OOH), peroxyester (RC (=O)-OO-R '), diacyl peroxide (RC (=O)-OOC (=O)-R '), peroxycarbonate (ROC (=O)-OOC (=O)-O-R '), peroxyketal (from the reaction between ketone and hydrogen peroxide or hydroperoxide), and mixtures thereof, R and R ' are independently aliphatic, alicyclic or aromatic groups. Examples of suitable peroxide compounds are dibenzoyl peroxide, dilauroyl peroxide, diisopropyl peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, cyclohexanone peroxide, methyl ethyl ketone peroxide, tert-butyl peroxyoctanoate, tert-butyl peroxybenzoate, dicumyl peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl permaleate, and mixtures thereof.

[0062] The copolymer of the present invention can be a single-stage copolymer. As used herein, a "single-stage copolymer" means a copolymer prepared in a single polymerization step, as opposed to a "multistage copolymer" prepared using multiple sequential polymerization steps. Therefore, a primary copolymer can exhibit a single phase and a single Tg.

[0063] The copolymer may have a biorenewable carbon content (%BRC) greater than 10, preferably greater than 30, more preferably greater than 50, and even more preferably greater than 70.

[0064] The weight average molecular weight (Mw) of the copolymer of the present invention is not particularly limited, but is preferably 20,000 g / mol to 120,000 g / mol, preferably 30,000 g / mol to 100,000 g / mol, and more preferably 40,000 g / mol to 90,000 g / mol from the viewpoints of, for example, handleability, viscosity, and mechanical properties. The molecular weight distribution (Mw / Mn) of the copolymer of the present invention, i.e., weight average molecular weight (Mw) / number average molecular weight (Mn), may be in the range of 1.01-5.5, preferably in the range of 1.05-5.

[0065] The number average molecular weight (Mn), weight average molecular weight (Mw), and molecular weight distribution (Mw / Mn) of the copolymer can be determined by gel permeation chromatography (GPC) using polystyrene standards, for example, as described in the Examples section below.

[0066] The glass transition temperature (Tg) of the copolymer of the present invention is not particularly limited, but is preferably in the range of -40°C to 50°C, preferably in the range of -30°C to 40°C, and more preferably in the range of -20°C to 30°C, calculated according to the Fox equation. The calculation formula is:

[0067]

[0068] Among them, W1 to W n is the mass fraction of each monomer used to obtain the copolymer; and T g1 To T gn is the glass transition temperature (in degrees Kelvin, "K") of the homopolymer corresponding to each monomer.

[0069] Composition

[0070] The composition of the present invention comprises the copolymer disclosed above.

[0071] In a first embodiment of the composition of the present invention, the composition comprises:

[0072] (A) the copolymer of the present invention; and

[0073] (B) at least one cross-linking agent selected from polyfunctional amines, hydrazides, aziridines, isocyanates, oxazoles, or epoxy compounds.

[0074] Such compositions may be heat curable compositions, i.e. compositions that cure by heating. In particular, the compositions may be applied to the surface of a substrate and cured by heating (e.g. oven drying). Once the composition cures, it may exhibit desired properties, such as adhesiveness.

[0075] At least one crosslinking agent (B) may be incorporated into the heat-curable composition to increase its cohesive strength. The crosslinking agent (B) includes a polyfunctional amine, a hydrazide, an aziridine, an isocyanate, an oxazole or an epoxy compound. An example of a polyfunctional aziridine compound is 1,1'-(1,3-phenylenedicarbonyl)-bis-(2-methylaziridine) (CAS No. 7652-64-4). Common polyfunctional isocyanate compounds are trimethylolpropane toluene diisocyanate, toluene diisocyanate and other compounds known in the art. The crosslinking agent may be added to the copolymer after polymerization and activated by heat during drying of the coated substrate. Such a composition may be particularly suitable for use as a PSA.

[0076] In a second embodiment of the composition of the present invention, the composition comprises:

[0077] (A) the copolymer of the present invention;

[0078] (C) at least one ethylenically unsaturated compound; and

[0079] Optionally (D) at least one free radical initiator.

[0080] Such a composition may be a radiation-curable composition, i.e., a composition that is cured by exposure to radiation, such as heat, UV energy, visible light, and / or electron beams. In particular, the radiation-curable composition may be cured by at least one of: (1) exposing the composition to UV energy and / or visible light; (2) exposing the composition to electron beams; (3) initiating polymerization by using redox-generated free radicals; (4) initiating polymerization by using thermally generated free radicals; or a combination thereof.

[0081] These first and second embodiments may be combined with each other.

[0082] The composition of the invention may comprise 5 to 90% by weight, preferably 10 to 90% by weight, in particular 10 to 80% by weight, of component (A), based on the total weight of the composition.

[0083] The composition of the invention may comprise 5 to 90% by weight, preferably 10 to 90% by weight, in particular 20 to 90% by weight, of component (C), based on the total weight of the composition.

[0084] In the radiation curable composition, component (C) may comprise or consist of at least one (meth)acryloyl-functional monomer or oligomer.

[0085] As used herein, the term "(meth)acryloyl-functionalized monomer" means a monomer comprising a (meth)acryloyl group, in particular an acryloyl group. The term "(meth)acryloyl-functionalized oligomer" means an oligomer comprising a (meth)acryloyl group, in particular an acryloyl group. The term "(meth)acryloyl" encompasses acrylate groups (-O-CO-CH=CH2), methacrylate groups (-O-CO-C(CH3)=CH2), acrylamide groups ( ), and methacrylamide ( ).

[0086] Component (C) may comprise or consist of: (C1) at least one (meth)acryloyl-functional monomer. Component (C1) may comprise a mixture of (meth)acryloyl-functional monomers.

[0087] The (meth)acryloyl-functional monomer may have a molecular weight of less than 600 g / mol, specifically 80 g / mol to 550 g / mol, more specifically 100 g / mol to 500 g / mol.

[0088] The (meth)acryloyl-functional monomer may have 1 to 6 (meth)acryloyl groups, in particular 1 to 4 (meth)acryloyl groups.

[0089] In particular, component (C1) may comprise or consist of at least one mono(meth)acryloyl-functionalized monomer. The mono(meth)acryloyl-functionalized monomer may advantageously act as a reactive diluent and reduce the viscosity of the composition of the invention. Further, it may impart viscoelastic properties required for adhesion or weather resistance to the cured composition.

[0090] Component (C1) may comprise or consist of at least one mono(meth)acrylate functionalized monomer, including but not limited to: mono(meth)acrylates of aliphatic alcohols (wherein the aliphatic alcohol may be linear, branched, or alicyclic, and may be a monool, a diol, or a polyol, provided that only one hydroxyl group is (meth)acrylated); mono(meth)acrylates of aromatic alcohols (e.g., phenol (phenol), including alkylated phenols); mono(meth)acrylates of alkylaryl alcohols (e.g., benzyl alcohol); oligomeric and polymeric diols such as diethylene glycol, triethylene glycol, dipropylene glycol, , tripropylene glycol, polyethylene glycol, and polypropylene glycol; mono(meth)acrylates of monoalkyl ethers of glycols and oligomeric glycols; mono(meth)acrylates of alkoxylated (e.g. ethoxylated and / or propoxylated) aliphatic alcohols (wherein the aliphatic alcohol may be linear, branched, or alicyclic, and may be a monool, a diol, or a polyol, provided that only one hydroxyl group of the alkoxylated aliphatic alcohol is (meth)acrylated); mono(meth)acrylates of alkoxylated (e.g. ethoxylated and / or propoxylated) aromatic alcohols (e.g. alkoxylated phenols); caprolactone mono(meth)acrylate; and mixtures thereof.

[0091] Specific examples of mono(meth)acrylate functionalized compounds include: methyl(meth)acrylate; ethyl(meth)acrylate; n-propyl(meth)acrylate; n-butyl(meth)acrylate; sec-butyl(meth)acrylate; isobutyl(meth)acrylate; 2-methylbutyl(meth)acrylate; 3-methylbutyl(meth)acrylate; n-hexyl(meth)acrylate; 4-methyl-2-pentyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; n-octyl(meth)acrylate; isooctyl(meth)acrylate; isononyl(meth)acrylate; n-decyl(meth)acrylate; isodec ... 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhexyl(meth)acrylate; 2-ethylhex 2-propylheptyl (meth)acrylate; n-dodecyl (meth)acrylate; tridecyl (meth)acrylate; tetradecyl (meth)acrylate; hexadecyl (meth)acrylate; C18-alkyl (meth)acrylate; C22-alkyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate; 2-hydroxypropyl (meth)acrylate and 3-hydroxypropyl (meth)acrylate; 2-methoxyethyl (meth)acrylate; 2-ethoxyethyl (meth)acrylate; 2-ethoxypropyl (meth)acrylate and 3-ethoxypropyl (meth)acrylate; tetrahydrofurfuryl (meth)acrylate; isobornyl (meth)acrylate; (meth) ) 2-(2-ethoxyethoxy)ethyl acrylate; cyclohexyl (meth)acrylate; tert-butyl cyclohexyl (meth)acrylate; glycidyl (meth)acrylate; benzyl (meth)acrylate; 2-phenoxyethyl (meth)acrylate; isobornyl (meth)acrylate; tricyclodecane methanol mono(meth)acrylate; phenol (meth)acrylate; nonylphenol (meth)acrylate; cyclic trimethylolpropane formal (meth)acrylate; trimethylcyclohexanol (meth)acrylate; diethylene glycol monomethyl ether (meth)acrylate; diethylene glycol monoethyl ether (meth)acrylate; diethylene glycol monobutyl ether (meth)acrylate Acrylates; triethylene glycol monoethyl ether (meth) acrylate; methoxy polyethylene glycol (meth) acrylate; (3-(2-hydroxyalkyl) oxazolidinone (meth) acrylate; (2,2-dimethyl-1,3-dioxolan-4-yl) methyl (meth) acrylate; (2-ethyl-2-methyl-1,3-dioxolan-4-yl) methyl (meth) acrylate; (1,3-dioxan-5-yl (meth) acrylate; (1,3-dioxolan-4-yl) methyl (meth) acrylate; glycerol carbonate (meth) acrylate; alkoxylated (i.e., ethoxylated and / or propoxylated) derivatives thereof; and combinations thereof.

[0092] Preferably, component (C1) comprises a mono(meth)acrylate-functionalized monomer having a branched alkyl or cyclic group, for example 2-ethylhexyl(meth)acrylate, tert-butyl(meth)acrylate, 2-phenoxyethyl(meth)acrylate, benzyl(meth)acrylate, isobornyl(meth)acrylate, tert-butylcyclohexyl(meth)acrylate, 3,3,5-trimethylcyclohexyl(meth)acrylate, dicyclopentadienyl(meth)acrylate, tricyclodecanemethanol mono(meth)acrylate, tetrahydrofurfuryl(meth)acrylate, cyclic trimethylolpropaneformyl(meth)acrylate (also known as 5-ethyl-1,3-dioxan-5-yl)methyl(meth)acrylate), (2,2-dimethyl-1,3-dioxolan-4-yl)methyl(meth)acrylate, (2-ethyl-2-methyl-1,3-dioxolan-4-yl)methyl(meth)acrylate. Such monomers can advantageously increase the Tg and adhesive properties of the cured composition compared to monofunctional alkyl (meth)acrylates having a linear alkyl group with the same number of carbon atoms.

[0093] Component (C1) may comprise or consist of at least one mono(meth)acrylamide functionalized monomer, including but not limited to: (meth)acrylamide; N-methyl(meth)acrylamide; N-ethyl(meth)acrylamide; isopropyl(meth)acrylamide; N,N-diethyl(meth)acrylamide; N-cyclohexyl(meth)acrylamide, N-cyclopentyl(meth)acrylamide; N-butoxymethyl(meth)acrylamide; N,N-dibutyl(meth)acrylamide; N-butyl(meth)acrylamide; diacetone(meth)acrylamide; N-(N,N-dimethylamino)ethyl(meth)acrylamide Amide; N,-(N,N-dimethylamino)propyl(meth)acrylamide; N,N-diethyl(meth)acrylamide; N,N-dimethyl(meth)acrylamide; N-octyl(meth)acrylamide; N-decyl(meth)acrylamide; N-dodecyl(meth)acrylamide; N-octadecyl(meth)acrylamide; N-isopropyl(meth)acrylamide; N-tert-butyl(meth)acrylamide; N-isobutyl(meth)acrylamide; N,N,3,3-tetramethylacrylamide; N-hydroxymethyl(meth)acrylamide; N-[2-hydroxyethyl](meth)acrylamide; N-phenyl(meth)acrylamide; acryloylmorpholine; and combinations thereof.

[0094] In a preferred embodiment, component (C1) may comprise or consist of a mixture of at least one mono(meth)acrylate-functional monomer and at least one mono(meth)acrylamide-functional monomer.

[0095] Component (C) may comprise 0 to 100 wt %, in particular 5 to 100 wt %, more in particular 10 to 100 wt %, even more in particular 20 to 100 wt % of component (C1), based on the total weight of component (C). In particular, component (C) may comprise 5 to 50 wt %, or 10 to 50 wt %, or 15 to 50 wt %, or 20 to 50 wt % of component (C1), based on the total weight of component (C). Alternatively, component (C) may comprise 50 to 100 wt %, or 55 to 100 wt %, or 60 to 100 wt %, or 65 to 100 wt % of component (C1), based on the total weight of component (C).

[0096] Component (C) may comprise or consist of: (C2) at least one (meth)acrylate functionalized oligomer. Component (C2) may comprise or consist of: a mixture of (meth)acrylate functionalized oligomers.

[0097] The (meth)acrylate functionalized oligomers may be selected to enhance the flexibility, strength, and / or modulus, among other properties, of the cured polymers prepared using the compositions of the present invention.

[0098] The (meth)acrylate functionalized oligomer may have 1 to 18 (meth)acrylate groups, specifically 2 to 6 (meth)acrylate groups, more specifically 2 to 6 acrylate groups.

[0099] The (meth)acrylate functionalized oligomer may have a number average molecular weight of 2,000 g / mol to 100,000 g / mol, preferably 3,000 g / mol to 90,000 g / mol, and more preferably 4,000 g / mol to 80,000 g / mol. The number average molecular weight of the oligomer may be determined by gel permeation chromatography (GPC) using polystyrene standards.

[0100] The (meth)acrylate functionalized oligomer may be selected from (meth)acrylate functionalized urethane oligomers (sometimes also referred to as "urethane (meth)acrylate oligomers", "polyurethane (meth)acrylate oligomers" or "carbamate (meth)acrylate oligomers"), (meth)acrylate functionalized epoxy oligomers (sometimes also referred to as "epoxy (meth)acrylate oligomers"), (meth)acrylate functionalized polyether oligomers (sometimes also referred to as "polyether (meth)acrylate oligomers"), (meth)acrylate functionalized polydiene oligomers (sometimes also referred to as "polydiene (meth)acrylate oligomers"), (meth)acrylate functionalized polycarbonate oligomers (sometimes also referred to as "polycarbonate (meth)acrylate oligomers"), and (meth)acrylate functionalized polyester oligomers (sometimes also referred to as "polyester (meth)acrylate oligomers"), and mixtures thereof.

[0101] In particular, component (C2) may comprise or consist of a (meth)acrylate-functionalized urethane oligomer, more preferably an acrylate-functionalized urethane oligomer.

[0102] Advantageously, the (meth)acrylate functionalized oligomer comprises a (meth)acrylate functionalized urethane oligomer having two (meth)acrylate groups, more preferably an acrylate functionalized urethane oligomer having two acrylate groups.

[0103] (Meth)acrylate functionalized urethane oligomers suitable for use in the compositions of the present invention can be prepared by reacting a polyisocyanate (e.g., an aliphatic, alicyclic, and / or aromatic diisocyanate or triisocyanate) with a polyol (e.g., a polyester polyol, a polyether polyol, a polycarbonate polyol, a polycaprolactone polyol, a polyorganosiloxane polyol, or a polydiene polyol such as a polybutadiene polyol, or a combination thereof) to form an isocyanate functionalized oligomer, which is then reacted with a hydroxyl functionalized (meth)acrylate (e.g., hydroxyethyl (meth)acrylate) to provide terminal (meth)acrylate groups. For example, the (meth)acrylate functionalized urethane oligomer can contain two, three, four, or more (meth)acrylate functional groups per molecule. As is known in the art, other addition sequences can also be practiced to prepare (meth)acrylate functionalized urethane oligomers. For example, a hydroxyl-functional (meth)acrylate can first be reacted with a polyisocyanate to obtain an isocyanate-functional (meth)acrylate, which can then be reacted with a polyol. Alternatively, all components can be combined and reacted simultaneously.

[0104] In a preferred embodiment, the (meth) acrylate functionalized carbamate oligomer comprises in its backbone: a hydrophobic portion derived from a polyolefin, a polydiene or a hydrogenated polydiene (e.g., polypropylene, polybutadiene, hydrogenated polybutadiene, polyisoprene or hydrogenated polyisoprene). The hydrophobic portion can be incorporated to prepare the (meth) acrylate functionalized carbamate oligomer by using polypropylene polyol, polybutadiene polyol, hydrogenated polybutadiene polyol, polyisoprene polyol or hydrogenated polyisoprene polyol. The example of hydrophobic (meth) acrylate functionalized carbamate oligomer is commercially available from Sartomer (particularly CN8899 NS, a difunctional carbamate acrylate oligomer). Adding hydrophobic (meth) acrylate functionalized carbamate oligomer in radiation curable compositions can improve the resilience properties of the film formed therefrom.

[0105] Based on the total weight of component (C), component (C) may contain 0 to 100% by weight, in particular 0 to 90% by weight, more particularly 0 to 85% by weight, even more particularly 0 to 80% by weight of component (C2). In particular, based on the total weight of component (C), component (C) may contain 0 to 50% by weight, or 0 to 40% by weight, or 0 to 30% by weight, or 0 to 25% by weight of component (C2). Alternatively, based on the total weight of component (C), component (C) may contain 50 to 100% by weight, or 55 to 90% by weight, or 60 to 90% by weight, or 65 to 90% by weight of component (C2).

[0106] In contrast to conventionally used tackifiers in adhesive compositions, such as styrenated terpenes, hydrocarbon resins, and polyisobutylenes, the copolymers of the present invention exhibit excellent compatibility with (meth)acrylate functionalized monomers and oligomers. Thus, the radiation curable compositions of the present invention have excellent compatibility between the ingredients and can be used to obtain optically clear adhesives or coatings.

[0107] The composition of the present invention may comprise 0 to 5 wt %, in particular 1 to 3 wt %, of component (D), based on the total weight of the composition.

[0108] The at least one free radical initiator (D) may be a photoinitiator, i.e., an initiator that generates free radicals when exposed to electromagnetic radiation such as UV light or visible light. Examples of photoinitiators are benzoin, benzoin ether, acetophenone, α-hydroxyacetophenone, benzyl, benzyl ketal, anthraquinone, phosphine oxide, acylphosphine oxide, α-hydroxyketone, phenylglyoxylate, α-aminoketone, benzophenone, thioxanthone, xanthone, acridine derivatives, phenazine derivatives, quinoxaline derivatives, triazine compounds, benzoyl formate, aromatic oximes, metallocenes, acylsilyl or acylgermanyl compounds, camphorquinone, polymer derivatives thereof, and mixtures thereof. Among these, phosphine oxides are preferred. Examples of commercially available photoinitiators include those sold under the trade names SpeedCure TPO and SpeedCure XKm from Sartomer.

[0109] Alternatively, the at least one free radical initiator (D) may be a peroxide initiator. The peroxide initiator may be activated by heating or by a reducing agent. The peroxide initiator may be as defined above for the polymerization initiator. Examples of suitable reducing agents are tertiary amines such as N,N-dimethylaniline, N-(4-methoxyphenyl)pyrrolidine and N-phenyldiethanolamine, sodium sulfite, or sodium pyrosulfite.

[0110] The radiation-curable compositions described herein can be applied and cured using conventional techniques, such as by directing UV light from a medium pressure mercury lamp through multiple layers. Alternatively, electron beam (EB) radiation can be used to cure the radiation-curable adhesive composition. When EB radiation is used, the composition may be free of free radical initiators (D).

[0111] In the radiation-curable composition of the present invention, the content of each component can be appropriately controlled according to factors such as target application and property requirements. As an example, based on the total weight of the composition, the radiation-curable composition may include or consist of:

[0112] 10 to 90% by weight, in particular 60 to 80% by weight, of (A) the copolymer according to the invention;

[0113] 10 to 90% by weight, in particular 20 to 40% by weight, of (C1) at least one mono(meth)acryloyl-functional monomer;

[0114] 0 to 5% by weight, in particular 1 to 3% by weight, of (D) at least one free-radical initiator.

[0115] In particular, the total weight of components (A), (C1) and (D) may account for 100% by weight of the radiation curable composition.

[0116] Alternatively, the radiation curable composition may comprise or consist of the following, based on the total weight of the composition:

[0117] 5 to 90% by weight, in particular 10 to 35% by weight of (A) the copolymer according to the present invention;

[0118] 5 to 90% by weight, in particular 15 to 35% by weight, of (C1) at least one mono(meth)acryloyl-functional monomer;

[0119] 5 to 90% by weight, in particular 30 to 74% by weight, of (C2) at least one (meth)acrylate-functional urethane oligomer; and

[0120] 0 to 5% by weight, in particular 1 to 3% by weight, of (D) at least one free-radical initiator.

[0121] For example, the radiation curable composition may comprise or consist of the following, based on the total weight of the composition:

[0122] 10 to 90% by weight, in particular 10 to 35% by weight, of (A) the copolymer according to the invention;

[0123] 10 to 90% by weight, in particular 15 to 35% by weight, of (C1) at least one mono(meth)acryloyl-functional monomer;

[0124] 10 to 90% by weight, in particular 30 to 74% by weight, of (C2) at least one (meth)acrylate-functional urethane oligomer; and

[0125] 0 to 5% by weight, in particular 1 to 3% by weight, of (D) at least one free-radical initiator.

[0126] In particular, the total weight of components (A), (C1), (C2) and (D) may account for 100% of the weight of the radiation curable composition.

[0127] In the third embodiment of the composition according to the present invention, the composition may include copolymer of the present invention and solvent (organic solvent or water). In the case of using an organic solvent as a solvent, adding an organic solvent can help adjust the viscosity of the composition to reach the viscosity required for application. In another case of using water as a solvent, the composition is an aqueous composition (or emulsion, latex, aqueous dispersion). Relative to the gross weight of the composition, the copolymer in the composition generally accounts for 5 to 90 weight %, preferably 10 to 75 weight %. On a dry basis, relative to the gross weight of the composition, the copolymer generally accounts for 5 to 50 weight % and preferably 20 to 40 weight %. The composition may further include other adhesives, such as silicone resins or silicates. When the solvent is an organic solvent, the composition may be used as a solvent-based coating composition or a solvent-based adhesive composition. When the solvent is water, the composition may be used as a waterborne coating composition or a waterborne adhesive composition.

[0128] This third embodiment may be combined with the first and / or second embodiment described above.

[0129] The above copolymers and compositions of the present invention can be used in a variety of applications, including automotive, consumer electronics and construction industries. As two standard examples, they can be used in the preparation of adhesives or coatings or as adhesives or coatings, which will be discussed in detail below.

[0130] Uses in adhesives

[0131] In the specification, "adhesive" or "adhesives" means a substance applied between two separate items to bond them together and resist their separation. Adhesive may also be called glue, sealant, cement, mortar, putty, glue, or paste.

[0132] The composition of the present invention can be used directly as an adhesive or used together with other raw materials to prepare an adhesive.

[0133] When used as adhesive, composition of the present invention can first be applied on the surface of the first substrate using conventional coating techniques (for example roller coating, brush coating, flow coating, dip coating, spin coating, spray coating, knife coating, spread coating, line coating, gravure coating, scraper coating and die coating). The thickness applied can be according to multiple factors, for example, the viscosity of specific application, composition and the property of substrate change. Subsequently the second substrate is joined to the surface, thereby setting up the high-strength bonding of joining two substrates. If necessary, the composition can be solidified under specific conditions (comprising temperature, time, radiation etc.) to form an adhesive film laminated between two substrates. The first substrate and the second substrate can be made of wood, metal, glass, cement, paper, textile, leather, plastics, foam or brick separately.

[0134] The adhesive or adhesive film formed by the composition of the present invention may exhibit pressure-sensitive properties and have an excellent balance of adhesive strength and cohesive strength.

[0135] The adhesive film formed by the composition of the present invention may have good mechanical properties. In some embodiments, the composition of the present invention may have a peel strength on a glass substrate or a stainless steel substrate in the range of 8 to 35 N / cm, preferably 10 to 30 N / cm when forming an adhesive film.

[0136] The adhesive film formed by the composition of the present invention can have good optical properties, making it suitable for use as an optically transparent adhesive. The adhesive film can have a transmittance of 90% or more, preferably 95% or more, as measured by a spectrometer. The film can have a haze of 0.8% or less, preferably 0.5% or less, as measured by a spectrometer. In particular, transmittance and haze can be measured by a spectrophotometer, such as described in the Examples section below.

[0137] The adhesive film formed by the composition of the present invention may exhibit a low dielectric constant, making it suitable for use in electronic products.

[0138] When used as adhesive, the composition of the present invention may further include materials commonly used in the art to impart or enhance the viscosity of adhesive, such as tackifier. The example of tackifier includes rosin, glycerol or pentaerythritol rosin ester, hydrogenated rosin, polyterpene resin such as polymerized β-pinene, coumarone-indene resin, "C5" and "C9" polymerized petroleum fractions, etc. In addition, when used as adhesive, the composition of the present invention may further include other additives to change the property of adhesive. Such additives include plasticizer, pigment, tackifier, filler such as glass or polymer bubble or bead (which may be expanded or unexpanded), hydrophobic or hydrophilic silica, calcium carbonate, glass or synthetic fiber, foaming agent, toughening agent, reinforcing agent, flame retardant, antioxidant and stabilizer. Add the additive that is enough to obtain the amount of required final properties. If other additives are used, then based on the dry weight of total copolymer (A), up to about 40% by weight, preferably less than 30% by weight, more preferably less than 5% by weight will be suitable.

[0139] Use in coatings

[0140] The term "coating" or "coatings" is understood to mean a substance applied to a substrate in the form of a film, the thickness of which is sufficient to change the appearance of the substrate, especially its optical properties, and / or to protect its surface, especially against scratches, moisture, dirt, or light. The term "coating composition" does not cover adhesive compositions, but may include paints, protective coatings, varnishes, and ink compositions, without this list being limiting. The substrate for coating may be made of wood, metal, glass, cement, paper, textiles, leather, plastics, foam, or brick.

[0141] The composition of the present invention can be used directly as a coating or used together with other raw materials to prepare a coating.

[0142] When used as a coating, the composition of the present invention can be applied to the surface of a first substrate using conventional coating techniques (e.g., roller coating, brush coating, flow coating, dip coating, spin coating, spray coating, knife coating, spread coating, line coating, gravure coating, blade coating, and die coating) to form a coating film under specific curing conditions (including temperature, time, radiation, etc.). The thickness of the coating film can vary according to a variety of factors, such as the specific application, the viscosity of the composition, and the properties of the substrate, and can be uniform or non-uniform. The cured coating film can be a dry film having a desired hardness.

[0143] The coating film formed by the composition of the present invention can have good optical transparency. By spectrometer measurement, the film can have a transmittance of 90% or more, preferably 95% or more. By spectrometer measurement, the film can have a haze of 0.8% or less, preferably 0.5% or less. In particular, transmittance and haze can be measured by a spectrophotometer, such as described in the Examples section below.

[0144] The composition may further comprise various additives selected from, for example, one or more pigments; one or more powdered fillers; one or more pH regulators; one or more dispersants and / or wetting agents, such as sodium polyphosphate, potassium polyphosphate or ammonium polyphosphate and naphthalene sulfonates; one or more thickeners, such as xanthan gum and cellulose derivatives; one or more defoamers; one or more film formers; one or more antifreeze agents; one or more flame retardants, in particular organophosphorus compounds, magnesium hydroxide, or aluminum hydroxide; one or more biocides; and mixtures thereof.

[0145] Products

[0146] The present application also provides an article comprising at least one film formed by the composition of the present invention. The article may be an electronic device, such as a flexible or foldable display device or a touch screen.

[0147] Example

[0148] The following examples illustrate the invention without limiting it.

[0149] Materials and methods

[0150] The following compounds were used in the examples:

[0151] Table 1.

[0152]

[0153] The following methods were used to measure the various properties in the examples:

[0154] Molecular weight and distribution

[0155] The number average molecular weight (Mn), weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the copolymer were determined by gel permeation chromatography (GPC) using polystyrene standards. The measurement conditions of GPC are given below.

[0156] Model: Agilent Technologies 1200 Series

[0157] -Chromatographic column: Edipse XDB-C18 / Edipse Plus C18

[0158] -Eluent: Tetrahydrofuran (THF)

[0159] -Flow rate: 0.45 mL / min

[0160] - Temperature: 40℃

[0161] -Injection volume and sample concentration: 5 µL, 10 mg / mL

[0162] -Detection: RI (Differential Refractometer)

[0163] -System for collecting and processing data: Waters Empower3

[0164] Tg

[0165] The Tg of the copolymer was calculated according to the Fox equation. The calculation formula is:

[0166]

[0167] Among them, W1~W n is the mass fraction of each monomer used to obtain the copolymer; and T g1 To T gn is the glass transition temperature (in degrees Kelvin, "K") of the homopolymer corresponding to each monomer.

[0168] Transmittance and Haze

[0169] The transmittance and haze were measured using a spectrophotometer (HunterLab ColorQuest XE). Sample preparation: The composition was coated on a float glass substrate having a thickness of 50 µm and then dried or exposed to a light source having a wavelength of 225 wm / cm 2 、2000mj / cm 2 UV dosed mercury lamp for curing.

[0170] Peel strength

[0171] Also called peel strength, peel force or adhesive strength.

[0172] For the peel strength on stainless steel substrate, samples were prepared by laminating SUS 304 plates, 100 μm thick adhesive and 100 μm PET film. If the adhesive composition is a UV-curable composition, the sample is subjected to UV exposure. The sample is then stored at room temperature for 24 hours. The peel strength is measured by peeling in a 180° direction at a speed of 300 / min at 23°C using a tensile tester (Shimadzu AGS-X).

[0173] For the peel strength on a glass substrate, the same procedure was performed as described above except that a glass plate was used instead of the SUS304 plate.

[0174] Retention

[0175] It is measured according to ASTM D4498. A tape of 50 micrometers in thickness and 25 mm in width is produced on a stainless steel (SUS304) plate, a load of 1000 g is hung, a temperature rise is set to 25°C and 70°C, and drop times at 25°C and 70°C are searched, respectively.

[0176] Aging test

[0177] The humidity heat test was performed at 85°C and 85% relative humidity (RH) using a BGD 897 / 100C from BIUGED.

[0178] Preparation of 2-OA

[0179] Secondary octanol (260.0 g), acrylic acid (158.0 g), heptane (198.0 g), p-methoxyphenol (1.35 g) and methanesulfonic acid (6.0 g) were added to a 4-necked round-bottom flask and mixed thoroughly at room temperature. A reflux condenser was installed on the 4-necked round-bottom flask and dry air was blown into it, and the mixture was slowly heated to reach reflux temperature (i.e., 100 to 120° C.). The mixture was kept at reflux for 10 hours, and then samples were taken every hour for water production and acid value. When the water production reached 39 mL and the acid value of the mixture was less than 23 mg KOH / g, the reaction was stopped. A transparent oil mixture of 2-OA, acrylic acid and heptane was obtained.

[0180] Preparation 2-MBA

[0181] 2-Methyl-1-butanol (260.0 g), acrylic acid (234.0 g), heptane (197.0 g), p-methoxyphenol (1.4 g) and methanesulfonic acid (7.0 g) were added to a 4-necked round-bottom flask and mixed thoroughly at room temperature. A reflux condenser was installed on the 4-necked round-bottom flask and dry air was blown into it, and the mixture was slowly heated to reach the reflux temperature (i.e., 100 to 120° C.). The mixture was kept at reflux for 10 hours, and then samples were taken every hour for water production and acid value. The reaction was stopped when the water production reached 56 mL and the acid value of the mixture was less than 24 mg KOH / g. A transparent oil mixture of 2-MBA, acrylic acid and heptane was obtained.

[0182] Preparation 3-MBA

[0183] 3-Methyl-1-butanol (260.0 g), acrylic acid (234.0 g), heptane (197.0 g), p-methoxyphenol (1.4 g) and methanesulfonic acid (7.0 g) were added to a 4-necked round-bottom flask and mixed thoroughly at room temperature. A reflux condenser was installed on the 4-necked round-bottom flask and dry air was blown into it, and the mixture was slowly heated to reach reflux temperature (i.e., 100 to 120° C.). The mixture was kept at reflux for 10 hours, and then samples were taken every hour for water production and acid value. The reaction was stopped when the water production reached 56 mL and the acid value of the mixture was less than 24 mg KOH / g. A transparent oil mixture of 3-MBA, acrylic acid and heptane was obtained.

[0184] Examples 1 to 11: Copolymers

[0185] The following Examples 1 to 11 relate to the preparation of copolymers, of which Examples 1 to 7 are according to the present invention and Examples 8 to 11 are comparative examples.

[0186] Example 1 (according to the present invention)

[0187] Toluene (52.0 g) and ethyl acetate (8.0 g) are added to a 4-neck round bottom flask and mixed thoroughly at room temperature, stirred and heated to 85°C. 2-OA (50.0 g), IBOA (56.5 g), AIBN (0.5 g) and toluene (20.0 g) are mixed and added at a constant rate over 90 minutes under dry nitrogen. The temperature is maintained at 85°C for a period of time, then heated to 95°C and maintained for 60 minutes after adding the mixture of 2-OA, IBOA, AIBN and toluene. A mixture of AIBN (0.2 g) and toluene (2.0 g) is then added. The mixture is maintained at 95°C for 2 hours, followed by GPC sampling. A transparent oil is obtained after cooling and filtering.

[0188] Example 2-11. The process according to Example 1 was repeated, wherein the composition of the monomer feed was set as presented in Table 2, Table 3 and Table 4.

[0189] The property data of the copolymers prepared in Examples 1 to 11, including %BRC, molecular weight and distribution, and Tg are shown in Tables 2 to 4.

[0190] The copolymers obtained in Examples 1 to 11 can be used directly as adhesives. A copolymer (prepared in Examples 1 to 11) was applied to a substrate (SUS 304 plate or glass layer) with a thickness of 100 μm and covered with a 100 μm PET film. After storage for 24 hours at room temperature, the intermediate layer will form an adhesive film. The transmittance, haze and peel strength of the adhesive film measured according to the test method described above are shown in Tables 2 to 4.

[0191] Table 2.

[0192]

[0193] Table 3.

[0194]

[0195] Table 4.

[0196]

[0197] According to the results shown in Tables 2 to 4, the combined use of at least one of 2-OA, 2-MBA and 3-MBA, and at least one of IBOA or IBMOA can prepare copolymers having high %BRC values ​​(>70) and at the same time good optical properties (almost transparent) and mechanical properties (good peel force on substrates such as glass and SUS304).

[0198] Examples 12 to 22: Radiation Curable Compositions

[0199] The following Examples 12 to 15 relate to radiation-curable compositions according to the present invention. For each of Examples 11 to 14, the raw materials were mixed by weight according to Table 5, coated on a PET film, and laminated with a PET release film. After exposure to UV light, the PET release film was removed and a cured adhesive film was obtained. For the peel strength test, the cured adhesive film was manually laminated to glass or SUS304 with a manual roller, and heavy pressure was applied to the exposed side of the cured adhesive film. The optical properties and peel strength of the cured adhesive film are shown in Table 5. In the raw material section of Table 5, E1, E2, E4, and E7 refer to the copolymers prepared in Example 1, Example 2, Example 4, and Example 7, respectively. Using a 225 mW / cm 2 , 2000 mJ / cm 2 UV exposure was performed with a mercury lamp with a UV dose.

[0200] Table 5.

[0201]

[0202] The following Examples 16 to 22 relate to radiation curable compositions with urethane acrylate oligomer CN8899 NS, wherein Examples 16 to 19 are according to the present invention and Examples 20 to 22 are comparative examples with conventional adhesion promoters.

[0203] For each of Examples 16 to 22, the raw materials were mixed in parts by weight according to Table 6, coated on a PET film and laminated with a PET release film. After exposure to UV light, the PET release film was removed to obtain a cured adhesive film. For the peel strength test, the cured adhesive film was manually laminated to a glass or stainless steel (SS) substrate using a hand roller, and heavy pressure was applied to the exposed side of the cured adhesive film. The optical properties and peel strength of the cured film are shown in Table 6. In the raw material section of Table 6, E1, E2, E4, and E7 represent the copolymers prepared in Example 1, Example 2, Example 4, and Example 7, respectively. By using a 225 mW / cm 2 , 2000 mJ / cm 2 UV exposure was performed with a mercury lamp with a UV dose.

[0204] Table 6.

[0205]

[0206] As shown in Table 6, when the copolymer of the present invention is used as a tackifier in a radiation-curable adhesive composition, it has good compatibility with the urethane acrylate oligomer (CN8899 NS) in the system. In addition, the cured adhesive film exhibits good optical properties and adhesive strength. However, conventional tackifiers show poor compatibility with the urethane acrylate oligomer (CN8899 NS). Due to poor compatibility, the systems of Comparative Examples 20 to 22 cannot be used as optically clear adhesives.

Claims

1. A copolymer obtained by polymerizing a monomer mixture, the monomer mixture comprising, based on the total weight of the monomer mixture: (a) 45 to 95% by weight, in particular 45 to 90% by weight, 48 to 80% by weight, or 50 to 70% by weight, of at least one monomer selected from 2-octyl (meth)acrylate, 2-methylbutyl acrylate, 3-methylbutyl acrylate, and mixtures thereof; (b) 5 to 55% by weight, in particular 10 to 55% by weight, 20 to 52% by weight, or 30 to 50% by weight, of isobornyl (meth)acrylate; (c) 0 to 5 wt %, in particular 0 to 2 wt %, 0 to 1 wt %, or even 0 wt % of at least one carboxyl-functional ethylenically unsaturated monomer; and (d) 0 to 30% by weight, in particular 0 to 20% by weight, 0 to 10% by weight, or 0 to 5% by weight of at least one ethylenically unsaturated monomer other than (a), (b) and (c).

2. The copolymer according to claim 1, wherein the copolymer has a biorenewable carbon content (%BRC) greater than 10, preferably greater than 30, more preferably greater than 50, and even more preferably greater than 70.

3. The copolymer according to claim 1 or 2, wherein the copolymer has a weight average molecular weight of 20,000 to 120,000 g / mol, preferably 30,000 to 100,000 g / mol, more preferably 40,000 to 90,000 g / mol.

4. The copolymer according to any one of claims 1 to 3, wherein the copolymer has a glass transition temperature calculated according to the Fox equation ranging from -40°C to 50°C, preferably from -30°C to 40°C, and more preferably from -20°C to 30°C.

5. The copolymer according to any one of claims 1 to 4, wherein component (a) consists of the following, based on the total weight of component (a): (a1) 1 to 99% by weight of 2-octyl (meth)acrylate; and (a2) 1 to 99% by weight of 2-methylbutyl acrylate and / or 3-methylbutyl acrylate.

6. The copolymer according to any one of claims 1 to 5, wherein the monomer mixture is substantially free of component (c).

7. A composition comprising the copolymer according to any one of claims 1 to 6.

8. The composition according to claim 7, wherein the composition comprises: (A) the copolymer according to any one of claims 1 to 6; and (B) at least one cross-linking agent selected from polyfunctional amines, hydrazides, aziridines, isocyanates, oxazoles, or epoxy compounds.

9. The composition according to claim 7 or 8, wherein the composition comprises: (A) the copolymer according to any one of claims 1 to 6; (C) at least one ethylenically unsaturated compound; and Optionally (D) at least one free radical initiator.

10. The composition according to claim 9, wherein component (C) comprises or consists of: (C1) at least one (meth)acryloyl-functional monomer, in particular at least one mono(meth)acryloyl-functional monomer, more particularly a mono(meth)acrylate-functional monomer having a branched alkyl or cyclic group.

11. The composition according to claim 9 or 10, wherein component (C) comprises or consists of: (C2) at least one (meth)acrylate-functionalized oligomer, in particular at least one (meth)acrylate-functionalized urethane oligomer, more in particular at least one (meth)acrylate-functionalized urethane oligomer comprising in its backbone a hydrophobic moiety derived from a polyolefin, a polydiene, or a hydrogenated polydiene.

12. The composition according to any one of claims 9 to 11, wherein the composition comprises: 10 to 90% by weight, in particular 60 to 80% by weight, of (A) a copolymer according to any one of claims 1 to 6; 10 to 90% by weight, in particular 20 to 40% by weight, of (C1) at least one mono(meth)acryloyl-functional monomer; 0 to 5% by weight, in particular 1 to 3% by weight, of (D) at least one free-radical initiator.

13. The composition according to any one of claims 9 to 11, wherein the composition comprises: 10 to 90% by weight, in particular 10 to 35% by weight, of (A) a copolymer according to any one of claims 1 to 6; 10 to 90% by weight, in particular 15 to 35% by weight, of (C1) at least one mono(meth)acryloyl-functional monomer; 10 to 90% by weight, in particular 30 to 74% by weight, of (C2) at least one (meth)acrylate-functional urethane oligomer; and 0 to 5% by weight, in particular 1 to 3% by weight, of (D) at least one free-radical initiator.

14. The composition according to claim 7 or any one of claims 8 to 13, wherein the composition comprises the copolymer according to any one of claims 1 to 6 and a solvent, wherein the solvent is an organic solvent or water.

15. Use of the composition according to any one of claims 7 to 14 in the preparation of an adhesive or a coating or as an adhesive or a coating.

16. An article comprising at least one film formed by curing the composition according to any one of claims 7 to 14, wherein the at least one film has a transmittance of 95% or more and a haze of 0.5% or less.

17. The article of claim 16, wherein the article is an electronic device, such as a flexible or foldable display device or a touch screen.

Citation Information

Patent Citations

  • Method for producing 2-octyl acrylate by direct esterification

    WO2013064775A1